2016
DOI: 10.1016/j.bmc.2016.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based design of a new series of N-(piperidin-3-yl)pyrimidine-5-carboxamides as renin inhibitors

Abstract: The action of the aspartyl protease renin is the rate-limiting initial step of the renin-angiotensin-aldosterone system. Therefore, renin is a particularly promising target for blood pressure as well as onset and progression of cardiovascular and renal diseases. New pyrimidine derivatives 5-14 were designed in an attempt to enhance the renin inhibitory activity of compound 3 identified by our previous fragment-based drug design approach. Introduction of a basic amine essential for interaction with the two aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…We have already found an attractive lead compound 1 with an IC 50 value of 4.6 nM against human plasma renin by our fragment-based (FBDD) and structure-based drug design (SBDD) efforts . The X-ray cocrystal structure of compound 1 bound to renin was examined in detail as the starting point for our next round of SBDD efforts (Figure ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We have already found an attractive lead compound 1 with an IC 50 value of 4.6 nM against human plasma renin by our fragment-based (FBDD) and structure-based drug design (SBDD) efforts . The X-ray cocrystal structure of compound 1 bound to renin was examined in detail as the starting point for our next round of SBDD efforts (Figure ).…”
mentioning
confidence: 99%
“…PK studies revealed that compound 1 has better oral bioavailability in rats than aliskiren ( 1 , 13.8%; aliskiren, 2.4%). The reasons for this difference were thought to arise from improved physiochemical characteristics such as MW (414 and 552), topological polar surface area (TPSA) (82 and 146), and number of rotatable bonds (nRB) (9 and 20, respectively) which are known as important predictors for BA. , However, compound 1 possesses the furan moiety, which could potentially be oxidized by CYP to form toxic metabolites. , We sought to replace this moiety with metabolically stable substituent through chemical modification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, among the pyrimidine derivatives, pyrimidine‐carboxamides represent a promising class of bioactive substances and have received much attention in the field of medicine. For example, 2‐thioxo‐1,2‐dihydro pyrimidine‐5‐carboxamides (I) have moderate antibacterial activity against Bacillus subtilis ; N ‐(piperidin‐3‐yl) pyrimidine‐5‐carboxamides (II) can be used as renin inhibitor; 1,2‐ dihydropyrimidine‐5‐carboxamide containing morpholine moiety (III) exhibits good antihypertensive activity; and di‐substituted amino pyrimidine‐5‐carboxamides (IV) synthesized by Liang behave as excellent BMX kinase inhibitors . Their structures are shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, N -based heterocycles are especially important since many of the biologically active compounds such as alkaloids, glycosides, and hormones as well as some of the clinically used drugs carry N -containing heterocycles in their chemical structures. 1,2 As one of the N -based heterocycles, the piperidine ring system has been shown to possess various pharmacological effects such as antibacterial, antifungal, 3−5 anti-HIV, 6 antileishmanial, 7 anticancer, 8,9 renin inhibitory, 10 diuretic, and natriuretic 11 effects. Another N -containing heterocyclic structure, benzimidazole, is also known to have the ability to interact with biomolecules of living systems.…”
Section: Introductionmentioning
confidence: 99%